Dynamic behavior of carbon nanotubes and basalt fiber reinforced coral sand cement mortar at high strain rates. (18th July 2022) - Qin, Yue; Xu, Dongsheng; Zhang, Shanshan; Fan, Xiaochun
Highlights: It investigated dynamic mechanical behavior of BF and CNT reinforced CSC mortars. It investigates CSC mechanical properties through SHPB tests and SEM analysis. Both BF-reinforced and CNT-reinforced specimens have optimal contents. GFRP can greatly improve the reinforcement effect of BF and CNT CSC specimens. Abstract: This study investigated the dynamic mechanical behavior of basalt fiber (BF) and carbon nanotube (CNT) reinforced coral sand cement (CSC) mortars. Based on the Split Hopkinson Pressure Bar (SHPB) tests and micro analysis, the stress–strain behavior, and failure mode of the CNT and fiber reinforced CSC specimens were quantitatively analyzed. The quantitative relationships among the dissipated energy density, impact air pressure, dynamic compressive strength, and incident energy were explored. Furthermore, the reinforcement effect of a glass fiber reinforced polymer (GFRP) tube on the BF reinforced specimens and CNTs reinforced specimens was also evaluated. It was found that the dynamic compressive strength and toughness of coral sand cement mortar were enhanced by CNT and BF with the maximum strength growth rate up to 106% and 73%, respectively. There was an optimal fiber content for the BF reinforced specimens and the CNTs reinforced specimens at a specific condition. In this study, the optimal fiber content of CNT and BF was 0.04% and 0.3%, respectively. The BF reinforced specimens and CNTs reinforced specimens hooped with GFRP tubes showed a significant improvement of dynamic compressive strength compared with those without GFRP tubes, with the maximum strength increase rate of up to 168% and 130%, respectively.